OA37 Compassionate classrooms: supporting teachers to support children living with grief and loss. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - Rhatigan, Jim; Richardson, Marie; McLoughlin, Kathleen
Abstract : Background: Milford Care Centre's social work service is often contacted by teachers following a death within the school community. The team recognised the need to engage in a more proactive, health-promoting manner to help teachers normalise the experience of grief and loss, empowering them to provide support to pupils following bereavement. Aim: To develop and evaluate a brief intervention for teachers, as part of Milford Care Centre's Compassionate Communities programme, to support children experiencing bereavement. Methods: A five-hour experiential workshop was developed and piloted with (1) a group of teachers and (2) staff working with early school completion programmes across the City. The teacher workshop was evaluated using a pre/post design measuring death anxiety and self-reported confidence. A qualitative evaluation, of both workshops will be presented from both the facilitator and participant perspective. Results: The pilot highlighted that the intervention is acceptable and demonstrated both a significant reduction in death anxiety and improvement in self-reported confidence for teachers who participated. Conclusions: The Compassionate Classrooms: Working with Grief and Loss intervention can reduce death anxiety and improve teachers' confidence. The intervention will be shared with the audience for local adaptation.